2006
DOI: 10.1016/j.pbb.2006.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic and convulsant effects of the delta opioid agonist SNC80 in rhesus monkeys

Abstract: Non-peptidic delta opioid receptor agonists are being evaluated for a wide range of clinical applications; however, the clinical utility of piperazinyl benzamide delta agonists such as SNC80 may be limited by convulsant activity. The purpose of the present study was to evaluate the electroencephalographic and convulsant activity produced by a high dose of 10 mg/kg SNC80 IM in rhesus monkeys. EEG and behavioral activity were examined in four adult male rhesus monkeys after IM administration of SNC80. Monkeys we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…SNC80 and (+)BW373U86 produce convulsions, however, most other systemically available agonists do not (Pradhan et al, 2011a). This deleterious effect is dependent on the activation of the delta opioid receptor (Comer et al, 1993; Broom et al, 2002b), and has been observed in mice, rats, and squirrel and rhesus monkeys (Dykstra et al, 1993; Broom et al, 2002a; Danielsson et al, 2006; Jutkiewicz et al, 2006). The convulsions produced by delta agonists like SNC80 or (+)BW373U86 are behaviorally similar, but weaker than those produced by 4 the epileptogenic drug pentylenetetrazol (Comer et al, 1993).…”
Section: Things To Consider When Examining the Behavioral Effects Of mentioning
confidence: 99%
“…SNC80 and (+)BW373U86 produce convulsions, however, most other systemically available agonists do not (Pradhan et al, 2011a). This deleterious effect is dependent on the activation of the delta opioid receptor (Comer et al, 1993; Broom et al, 2002b), and has been observed in mice, rats, and squirrel and rhesus monkeys (Dykstra et al, 1993; Broom et al, 2002a; Danielsson et al, 2006; Jutkiewicz et al, 2006). The convulsions produced by delta agonists like SNC80 or (+)BW373U86 are behaviorally similar, but weaker than those produced by 4 the epileptogenic drug pentylenetetrazol (Comer et al, 1993).…”
Section: Things To Consider When Examining the Behavioral Effects Of mentioning
confidence: 99%
“…The first non-peptidic agonists BW373U86 and SNC80 were described to mediate brief and non-lethal convulsions in rodents [5, 6]. In addition, pro-convulsive effects of SNC80 were also reported in rhesus monkeys [7]. New agonists were developed with less or no adverse effects on epileptic thresholds, such as ADL5859, ADL5747 [8, 9] or KNT-127 [10] for example.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the demonstration of an antiepileptic effect following DOR activation in some studies [115118], several other reports showed opposite results. For example, SNC80, a putative DOR agonist, is proconvulsive [119, 120] though it is reported to inhibit Na + channel activity [80]. The reasons for the complex and mixed effects of the δ -opioid system on seizures are not well clarified yet, but could be partially related to multiple factors like animal species (e.g., proconvulsive in rats but has little effect in rhesus monkeys) [119–121], seizure types, the methods of drug administration [122], dose used [123], target neurons, and so forth (also see [1]).…”
Section: Discussionmentioning
confidence: 99%
“…DOR activation in the granule cells inhibits voltage-gated Na + channels and thus lowers the excitability of granule neurons [80], which reduces excitatory transmission in the epileptic network and subsequently suppresses seizures. However, DOR activation in inhibitory interneurons leading to the inhibition of Na + channels, as observed by Remy et al [80] in granule neurons, may result in facilitation, rather than suppression, of seizures via postsynaptic deinhibition [126, 127], as has been observed [119, 120]. Therefore, selective activation/inhibition of the opioid system in certain locations of the epileptic networks with acupuncture therapy is critical but also challengeable for the therapeutic outcome.…”
Section: Discussionmentioning
confidence: 99%